If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 = (3 + -2w)(w) Reorder the terms for easier multiplication: 65 = w(3 + -2w) 65 = (3 * w + -2w * w) 65 = (3w + -2w2) Solving 65 = 3w + -2w2 Solving for variable 'w'. Reorder the terms: 65 + -3w + 2w2 = 3w + -3w + -2w2 + 2w2 Combine like terms: 3w + -3w = 0 65 + -3w + 2w2 = 0 + -2w2 + 2w2 65 + -3w + 2w2 = -2w2 + 2w2 Combine like terms: -2w2 + 2w2 = 0 65 + -3w + 2w2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. 32.5 + -1.5w + w2 = 0 Move the constant term to the right: Add '-32.5' to each side of the equation. 32.5 + -1.5w + -32.5 + w2 = 0 + -32.5 Reorder the terms: 32.5 + -32.5 + -1.5w + w2 = 0 + -32.5 Combine like terms: 32.5 + -32.5 = 0.0 0.0 + -1.5w + w2 = 0 + -32.5 -1.5w + w2 = 0 + -32.5 Combine like terms: 0 + -32.5 = -32.5 -1.5w + w2 = -32.5 The w term is -1.5w. Take half its coefficient (-0.75). Square it (0.5625) and add it to both sides. Add '0.5625' to each side of the equation. -1.5w + 0.5625 + w2 = -32.5 + 0.5625 Reorder the terms: 0.5625 + -1.5w + w2 = -32.5 + 0.5625 Combine like terms: -32.5 + 0.5625 = -31.9375 0.5625 + -1.5w + w2 = -31.9375 Factor a perfect square on the left side: (w + -0.75)(w + -0.75) = -31.9375 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 5g-4(-5-3g)=1-1g | | w/2-34=53 | | 2w^2-3w+65=0 | | m=(12-3)/(11+1) | | 9x-1=3+8x | | 275=10(x-50)+75 | | 65=3w-2w^2 | | 3x+7=4x+8 | | 4(3m-10)-6(7m-6)=74 | | f=10(275-50)+75 | | 16=x+15 | | 5+5v=4+5v | | =5m(3m^3-4m)(7m^3-2m^2+5m+1) | | -1(2x-2y)=-1(-4) | | n+19=38 | | -2x+28+6x=42 | | f(2)=8x+3 | | 7+4x=34+4 | | 4+3y=-11 | | 7x+18=25 | | -2(-x-y)=-1(-14) | | 7x+12y=-16 | | 9u-47=2u-4 | | x-3(x+1)=6y-5x | | x^4+4x^2-7=0 | | 1=18+a | | (x+3)(x+5)(x-7)(x-9)=1792 | | 3x=f(w+5)+8 | | (x+3)(x+5)(x-7)(x-9)=0 | | f(w+5)=3x-8 | | 3x-4-5x=-3x-2 | | 36=14x-13x+8 |